Musculoskeletal disorders, work related factors and pain beliefs among visual-display-unit users - Redivo, Vanessa (My University, 2019)
Musculoskeletal disorders (MSD) in the work place have increased with the use of visual-display-units (VDU). The aim of this study was to assess factors that influence MSD in VDU users in South Africa. This cross-sectional, observational study included one hundred and thirty-six (136) participants working with VDU for more than four hours a day and for at least 12 months. All participants completed self-reported questionnaires (demographics, MSD, work-related psychosocial factors) and an evaluation of work-station ergonomic risk factors. Participants with work-related MSD, completed the Fear Avoidance Beliefs Questionnaire (FABQ) and Pain Beliefs Perception Inventory (PBPI). Participants without work-related MSD were a reference group. Over-commitment was significantly higher (p=0.041) in the MSD group than in the reference group. Participants exercising four to five times per week were 2.47 times more likely to be in the reference group, with no MSD. There was no evidence of altered beliefs in the FABQ and PBPI within the MSD group. Over-commitment is an indication of intrinsic factors and personal characteristics. Interventions to address over-committed individuals may be needed to assist with MSD management. Further research is imperative before treatment plans can be generalised.
A dissertation submitted to the faculty of health sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science Physiotherapy Gauteng, 2019
Keywords: Musculoskeletal system--Diseases; Video display terminals